Koordinasi Wewenang Komisi Pemberantasan Korupsi (KPK) dengan Penegak Hukum Lainnya dalam Melakukan Penyidikan Tindak Pidana Korupsi - Ni Putu Gita Loka Chindiyana Dewi; I Nyoman Sujana; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Corruption is a problem in the economy of every nation in the world, whether in Government or private environments. With the promulgation of Act No. 31 of the year 1999 Jo Act No. 20 year 2001. The Government in the year 2002 through Law – Law Number 30 year 2002 about corruption eradication Commission formed corruption eradication Commission (KPK) which is a specialized agency in dealing with the special corruption. At issue is how the authorities of the corruption eradication Commission (KPK) in conducting the investigation, the crime of corruption? And how coordination between the corruption eradication Commission (KPK) and other law enforcement agencies in conducting the investigation, the crime of corruption? The study used is the normative legal research i.e. research examines law is a law written from various aspects, but does not examine aspects of applied or implementation. Approach this research method by means of reviewing all laws, understanding the hierarchy of principles and legislation. The conclusion in May of this research is that in regards to the investigation of criminal acts of corruption, the corruption eradication Commission (KPK) has authority that is doing the coordination and supervision that can perform the takeover against investigation or the prosecution conducted by the Police and the Prosecutor's Office. But in the relationship between the coordination with other law enforcement agencies KPK still haven't made good cooperation.